Inkjet printing of Function-Spacer-Lipid (FSL) biomolecules - Barr, K; Diegel, O; Parker, S; Henry, SM (AUT University, 2011)
FSL constructs (KODE Biotech Limited) consist of 3 parts: a functional head group (F), a spacer (S) and a lipid tail (L). The lipid tail acts as an anchor to localise the functional head group to a lipophilic surface, e.g. a cell membrane. In addition to satisfying the requirement for biocompatibility, the ability of the FSL constructs to disperse easily in water allows solutions of the constructs to be substituted for the ink in inkjet printer cartridges. FSL constructs can then be printed onto solid surfaces using a standard desktop printer and are being used to develop prototype diagnostic assays (Bovin et al, 2011). The constructs can be printed as words or in desired patterns. FSL constructs comprising ABO blood group antigens or biotin as the functional head groups (F) have been printed onto silica, nitrocellulose and paper. The printed constructs have then been used to identify antibodies in different biological samples. The inkjet printing of FSL constructs provides the advantage that multiple antibodies can be identified and quantified in the same reaction well. The inkjet printing of FSL constructs is proving to be a fast, inexpensive and flexible method of producing diagnostic assays.
Keywords: Bioprinting; 3D printing; tissue engineering; inkjet printing of biomaterials